Morphological, optical and electrical properties of spray coated zinc ethyl xanthates for decomposition within a poly(3-hexylthiophene-2,5-diyl) matrix - Bishop, Matthew; Akinwolemiwa, Bamidele; Zhang, Lun; Peng, Chuang; Hu, Di (2019)
This work investigates the deposition of hybrid layers, for next generation in energy conversion, via spray coating. Understanding the effect that this deposition procedure has on these layers could lead to the rapid development of these technologies, for both laboratory applications and commercialisation. Synthesised zinc ethyl xanthate and poly(3-hexylthiophene-2,5-diyl) was spray-coated on substrates and heated to a temperature of 160 oC, to the hybrid film. Optical, morphological and conductive properties of these films were investigated and linked to the spray coating duration. It was revealed that shorter-duration spray times led to relatively low conductivity and smoother films, moreover, an increase in spraying duration also led to an increase in conductivity, but with increased roughness, from 6.178 nm to 8.317 nm. As the spray time was further increased factors, including film layering effects, led to a gradual decrease in conductivity accompanied by a decrease in the roughness. Smoother films were shown to result in higher light absorption, characterised by wider band gaps, which could be due to the crystal structure of the inorganic phase. The controllability of this rapid, facile, and inexpensive spray deposition process was then demonstrated in fabrication of prototype photovoltaic devices.